Single-component photovoltaic structural sealant and preparation method thereof
By preparing a single-component photovoltaic structure sealant, the surface drying time and deep curing effect are optimized by the collaborative components, the existing sealant has long curing time, short storage period, poor mechanical properties and bonding properties, and high efficiency curing and good durability in the application environment of photovoltaic glue are achieved.
Patent Information
- Application Number
- CN202411677949.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
During the application process, existing sealants have long curing time, short storage period, poor mechanical properties and bonding properties, and poor durability, which are susceptible to environmental factors to degrade performance.
By collaborating with different proportions and types of components, a single-component photovoltaic structural sealant is prepared, including hydroxy-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, crosslinking agent, coupling agent, catalyst and dissolution aid, to optimize the surface drying time and deep curing effect.
It achieves excellent surface drying time and deep curing effect in photovoltaic glue application environment, increases the elongation and toughness of the colloid, improves industrial production efficiency, and maintains a good curing depth at different temperatures and humidity, and has excellent weathering and aging resistance.
Smart Images

Figure BDA0005147507040000051 
Figure BDA0005147507040000052 
Figure BDA0005147507040000061
Abstract
Description
Technical Field
[0001] The invention belongs to functional materials, and in particular relates to a single-component photovoltaic structure sealant and a preparation method thereof. Technical Background
[0002] With the rapid development of solar cell modules, the use of adhesive bonding technology to achieve cell encapsulation, frame bonding and sealing, junction box and backplane bonding, junction box potting, and busbar backplane incision sealing has become a development trend and has been adopted by more and more manufacturers. The technical and economic benefits achieved by the application of adhesives have attracted great attention and concern from the solar cell module industry. Organic silicone adhesives The basic structural unit of organic silicone products is composed of silicon-oxygen chain links, and the side chains are connected to various other organic groups through silicon atoms. Therefore, the structure of organic silicone products contains both "organic groups" and "inorganic structures". This special composition and molecular structure makes it combine the characteristics of organic matter with the functions of inorganic matter. Compared with other polymer materials, the most outstanding properties of organic silicone products are: temperature resistance, weather resistance, electrical insulation performance, physiological inertness, low surface tension and low surface energy. Single-component silicone, translucent paste-like room temperature curing adhesive, is a high-performance elastomer formed by natural curing. It has excellent resistance to heat and cold, aging and electrical insulation properties, and has good adhesion to most metal and non-metal materials. Two-component silicone dealcohol condensation type. Does not contain byproducts such as acid and ketoxime, does not corrode metals and plastics; does not have curing inhibition or poisoning; has a low linear expansion coefficient; cures at room temperature; has good adhesion to junction boxes of various materials.
[0003] The existing sealants have the following main disadvantages during application: long curing time, short storage period of single-component structural sealants, relatively poor mechanical properties and bonding properties with substrates. It takes about 2-3 days for single-component structural sealants on the market to fully cure; poor durability. Existing silicone structural sealants are easily affected by the surrounding environment during long-term use, such as ultraviolet rays, temperature, humidity changes, etc. After a period of use, their mechanical properties and bonding properties will gradually decrease, and cracking, discoloration, hardening and falling off will occur. This is obviously not good for the photovoltaic field that requires long-term use. Summary of the invention
[0004] The present invention discloses a single-component photovoltaic structural sealant and a preparation method thereof. By coordinating components of different proportions and types, the obtained finished products are tested, and it is found that in the application environment of photovoltaic glue, the surface drying time and deep curing effect of the product of the present invention are relatively excellent, the elongation at break of the colloid can be increased, and the toughness can be improved. Furthermore, the product of the present invention improves the efficiency required for industrial production, and the curing depth of the photovoltaic glue product is good under different temperatures and humidities.
[0005] The present invention adopts the following technical solution:
[0006] A single-component photovoltaic structural sealant comprises hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, a crosslinking agent, a coupling agent, a catalyst and a dissolving aid.
[0007] Preferably, the present invention uses hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, a cross-linking agent, a coupling agent, a catalyst, and a dissolution aid as raw materials to form a single-component photovoltaic structural sealant, which has excellent surface drying time and deep curing effect, can increase the elongation at break of the colloid, and improve toughness.
[0008] The invention discloses a preparation method of the above-mentioned one-component photovoltaic structure sealant, comprising the following steps: mixing hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, a cross-linking agent, a coupling agent, a catalyst, and a dissolving aid to obtain the one-component photovoltaic structure sealant.
[0009] Preferably, the preparation method of the above-mentioned one-component photovoltaic structure sealant disclosed in the present invention comprises the following steps: hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, silicone oil and magnesium hydroxide are vacuum mixed to obtain viscous colloid A; then white carbon black and a cross-linking agent are added to the viscous colloid A, and vacuum stirred to obtain colloid B; then a mixture of a coupling agent, a catalyst and acetylacetone is added to colloid B to obtain colloid C, and colloid C is continuously vacuumed to obtain a finished one-component photovoltaic structure sealant.
[0010] In the present invention, the viscosity of hydroxyl-terminated dimethylsiloxane is 15000Pa·s to 18000Pa·s; the viscosity of silicone oil is 100Pa·s to 200Pa·s; for example, the viscosity of hydroxyl-terminated dimethylsiloxane is 15000Pa·s or 18000Pa·s; the viscosity of silicone oil is 100Pa·s or 200Pa·s; unless otherwise specified, the viscosity is data at 25°C.
[0011] In the present invention, the white carbon black is hydrophobic to avoid the crosslinking agent from reacting due to hydrophilicity; the crosslinking agent is one or more of methyl tributylanoxime silane, vinyl tributylanoxime silane and methyl triethoxy silane, and the addition ratio is 1-5 parts.
[0012] In the present invention, the coupling agent is one or more of vinyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-n-butyl-3-aminopropyltrimethoxysilane, and aminosilane polymer.
[0013] In the present invention, the catalyst is an organic tin compound, including one or two of dibutyltin diacetate and dibutyltin dilaurate.
[0014] In the present invention, the dissolution aid is acetylacetone.
[0015] In the present invention, the weight ratio of hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, crosslinking agent, coupling agent, catalyst and acetylacetone is 100: (10-30): (70-90): (10-15): (0.1-0.3): (10-15): (1-3): (1-5): (1-5): (0.1-0.5): (0.1-0.5).
[0016] Preferably, the weight ratio of hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, cross-linking agent, coupling agent, catalyst and acetylacetone is 100:(15-25):(75-85):(10-15):(0.1-0.3):(10-15):(1-3):(1-3):(2-4):(0.2-0.4):(0.2-0.4).
[0017] The present invention discloses a solar energy module, which uses the above-mentioned single-component photovoltaic structure sealant as an adhesive; as common sense, the solar energy module also includes other conventional components.
[0018] The present invention discloses the application of the above-mentioned single-component photovoltaic structural sealant in photovoltaic bonding. Further, the present invention discloses the application of the above-mentioned single-component photovoltaic structural sealant in the preparation of photovoltaic bonding materials.
[0019] The one-component structural sealant of the present invention has many advantages: excellent sealing performance and electrical performance, maintaining excellent anti-puncture performance under various harsh conditions, maintaining good mechanical and electrical properties in a wide temperature range; excellent weather resistance, being able to resist the adverse effects of ultraviolet light, ozone, moisture, acid and alkali when used outdoors, and having good aging resistance; excellent yellowing resistance, passing aging and UV aging tests without yellowing; fast curing speed, being able to be completely cured within 1 day at room temperature; good thixotropy and deformation resistance, having a unique rheological system, good thixotropy and deformation resistance; high and low temperature resistance, with little performance change in the range of -50°C to 220°C and better stability; excellent impact resistance, having good anti-seismic, mechanical shock and thermal shock resistance functions; good electrical insulation, being able to maintain excellent anti-puncture performance under various harsh conditions, being pollution-free, corrosion-free, safe and environmentally friendly. DETAILED DESCRIPTION
[0020] By coordinating components of different proportions and types and testing the finished products, it was found that in the application environment of photovoltaic adhesive, the surface drying time and deep curing effect of the product of the present invention are relatively excellent, the elongation at break of the colloid can be increased, and the toughness can be improved. Furthermore, the product of the present invention improves the efficiency required for industrial production, and the curing depth of the photovoltaic adhesive product is good under different temperatures and humidities.
[0021] The preparation method of the above-mentioned one-component photovoltaic structure sealant disclosed in the present invention comprises the following steps: adding hydroxyl-terminated dimethylsiloxane of a certain viscosity to heavy calcium carbonate, light calcium carbonate, titanium dioxide, silicone oil and magnesium hydroxide in a planetary mixer in a certain proportion and performing vacuum stirring for 0.5 to 5 hours to obtain a viscous colloid A; then adding a certain amount of white carbon black and a cross-linking agent to A in batches and vacuum stirring for 0.5 to 5 hours to obtain a colloid B; then mixing a certain amount of a coupling agent and a catalyst and adding them to the colloid B to obtain a colloid C, and continuing to vacuum the colloid C for 0.5 to 2 hours to obtain a finished one-component photovoltaic structure sealant.
[0022] As an example, a method for preparing a one-component photovoltaic structure sealant comprises the following steps:
[0023] (1) Adding hydroxyl-terminated dimethylsiloxane of a certain viscosity to heavy calcium carbonate, light calcium carbonate, titanium dioxide, silicone oil, and magnesium hydroxide in a certain proportion and mixing them in a vacuum to obtain colloid A, wherein the hydroxyl-terminated dimethylsiloxane has a viscosity of 15000 Pa·s or 18000 Pa·s and is used in a proportion of 100 parts (the following proportion bases are all calculated in parts, and unless otherwise specified, parts in the present invention refer to parts by weight), the heavy calcium carbonate is used in a proportion of 10-30 parts, and the light calcium carbonate is used in a proportion of 70-90 parts. The proportion of titanium dioxide is 10-15 parts, the proportion of magnesium hydroxide is 0.1-0.3 parts, and after mixing and stirring for 10-60 minutes, 10-15 parts of 100Pa·s or 200Pa·s silicone oil are added. After mixing evenly, the planetary mixer is heated to 130-140°C and vacuum mixed again for 1-2 hours. The vacuum degree is -0.1MPa to -0.15MPa. The water content of the colloid after mixing is <0.2%, which is called colloid A. After completion, it is cooled to room temperature under low temperature drying conditions for standby use;
[0024] (2) adding a certain amount of white carbon black and a crosslinking agent to colloid A in batches and vacuum stirring for 0.5-1.5 hours to obtain colloid B, wherein the white carbon black is a hydrophobic type, and the addition ratio is 1-3 parts to avoid the crosslinking agent from reacting due to hydrophilicity; the crosslinking agent is a methyl tributylan oxime silane, a vinyl tributylan oxime silane, a methyl triethoxy silane or a mixture thereof, and the addition ratio is 1-5 parts;
[0025] (3) A certain amount of coupling agent, catalyst and acetylacetone are mixed and then added to colloid B to obtain colloid C, wherein the coupling agent is one or a mixture of vinyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-n-butyl-3-aminopropyltrimethoxysilane, and aminosilane polymer, and the addition amount is 1-5 parts; the catalyst is an organic tin compound, including one or two of dibutyltin diacetate and dibutyltin dilaurate, and the addition amount is 0.2-0.4 parts; the addition amount of acetylacetone is 0.2-0.4 parts; after vacuum stirring for 0.5-1.5 hours, the finished single-component photovoltaic structure sealant is obtained by dispensing and discharging.
[0026] In addition to base materials such as siloxane, silicone oil, and calcium carbonate, crosslinking agents, coupling agents, and catalysts are the main auxiliary materials of sealants. Different addition ratios will have a serious impact on the performance of sealants. The present invention coordinates different proportions and types of base materials and auxiliary material components, and tests the obtained finished products. It is found that in the application environment of photovoltaic glue, the curing effect of the product of the present invention is relatively excellent.
[0027] Various exemplary embodiments of the present invention are now described in detail, which should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art in the field of the present invention. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. The raw materials used in the present invention are existing products that meet the conventional requirements of solar cells, and the specific preparation operations and performance tests are all conventional techniques. The water content of heavy calcium carbonate is <0.2%, and the water content of light calcium carbonate is <0.3%; the silicone oil is 107 silicone resin, which is a standard product with different viscosities.
[0028] Embodiment 1
[0029] A method for preparing a single-component photovoltaic structure sealant, the steps are as follows:
[0030] (1) After mixing hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, and magnesium hydroxide for 30 minutes, silicone oil was added and mixed evenly. The planetary mixer was heated to 135° C. and mixed again under vacuum for 1 hour. The vacuum degree was -0.098 MPa. The mixture was naturally cooled to about 35° C. to obtain colloid A.
[0031] The viscosity of hydroxyl-terminated dimethylsiloxane is 18000Pa·s, and the usage ratio is 100 parts (the following ratio bases are all calculated in parts, each part is 1Kg); the usage ratios of heavy calcium carbonate are 30, 20, and 10 parts respectively, and the usage ratios of light calcium carbonate are 90, 80, and 70 parts respectively; silicone oil is 200Pa·s, and the usage ratio is 15 parts; titanium dioxide is 12 parts, and magnesium hydroxide is 0.2 parts.
[0032] The effects of different proportions of heavy and light calcium on the quality of the base material are shown in Table 1. By testing the base material colloid A, it was found that 20 parts of heavy calcium and 80 parts of light calcium had the best comprehensive performance. In the following experiments, unless otherwise specified, 20 parts of heavy calcium and 80 parts of light calcium were used.
[0033] Table 1 Different proportions of heavy and light calcium base materials
[0034]
[0035] Thixotropy and extrusion properties are standard methods of national standard GB / 16776.
[0036] (2) In a dual planetary power mixer, white carbon black and a crosslinking agent were added to colloid A in two batches at an interval of 30 minutes, and the mixture was vacuum stirred for 1 hour to obtain colloid B; the white carbon black was added in a proportion of 2 parts; the crosslinking agent was methyl tributylidene oxime silane, and the addition proportion was 1 part (sample ①), 2 parts (sample ②) or 3 parts (sample ③).
[0037] (3) After the coupling agent, catalyst and acetylacetone are mixed, they are added to colloid B, and the mixture is stirred for 1 hour to obtain colloid C, i.e., the finished single-component photovoltaic structural sealant; wherein the coupling agent is vinyltrimethoxysilane, the addition amount is 3 parts, the catalyst is dibutyltin diacetate, the amount is 0.3 parts, and acetylacetone is a dissolving aid, the amount is 0.3 parts.
[0038] The test results of the product colloid C prepared with different proportions of cross-linking agents are shown in Table 2. Through the test results of different proportions of cross-linking agents, when the cross-linking agent is 2 parts, the strength and bonding performance of the colloid are excellent; in the following experiments, unless otherwise specified, 2 parts of methyl tributylidene silane are used.
[0039] Table 2 Quality test results of cross-linking agent products with different proportions
[0040]
[0041] Example 2 Variation of Catalyst
[0042] The product solutions of catalyst preparation of different solutions are as follows:
[0043] ① Referring to Example 1, colloid B is obtained, and the coupling agent, catalyst, and acetylacetone are mixed and added to colloid B, and colloid C is obtained after stirring for 1 hour, i.e., the finished single-component photovoltaic structure sealant; wherein the coupling agent is vinyltrimethoxysilane, and the addition amount is 3 parts, the catalyst is dibutyltin diacetate, and the amount is 0.2 parts, and acetylacetone is a dissolution aid, and the amount is 0.3 parts. ② Referring to Example 1, colloid B is obtained, and the coupling agent, catalyst, and acetylacetone are mixed and added to colloid B, and colloid C is obtained after stirring for 1 hour, i.e., the finished single-component photovoltaic structure sealant; wherein the coupling agent is vinyltrimethoxysilane, and the addition amount is 3 parts, the catalyst is dibutyltin dilaurate, and the amount is 0.2 parts, and acetylacetone is a dissolution aid, and the amount is 0.3 parts. ③ Referring to Example 1, colloid B is obtained, and the coupling agent, catalyst, and acetylacetone are mixed and added to colloid B, and colloid C is obtained after stirring for 1 hour, i.e., the finished single-component photovoltaic structural sealant; wherein the coupling agent is vinyltrimethoxysilane, the addition amount is 3 parts, the catalyst is 0.2 parts of a mixture of dibutyltin dilaurate and dibutyltin diacetate, the mass ratio of the two catalysts is 1:1, and acetylacetone is a dissolving aid, and the amount is 0.3 parts.
[0044] ④ Referring to Example 1, colloid B is obtained, and the coupling agent, catalyst, and acetylacetone are mixed and added to colloid B. After stirring for 1 hour, colloid C is obtained, which is the finished one-component photovoltaic structure sealant; wherein the coupling agent is vinyltrimethoxysilane, the addition amount is 3 parts, the catalyst is dibutyltin diacetate, the amount is 0.5 parts, and acetylacetone is a dissolving aid, the amount is 0.3 parts.
[0045] The test results are shown in Table 3. When the cross-linking agent is 2 parts and the coupling agent is 3 parts, the strength and bonding performance of the colloid are excellent. The cross-linking agent uses methyl tributyl ketoxime silane, the dosage is 2 parts, and the dosage of white carbon black is 2 parts.
[0046] Table 3 Results of product curing test with different catalysts
[0047]
[0048] Results: After testing the finished products obtained after testing different proportions and different types of catalysts, it was found that in the application environment of photovoltaic glue, when the ratio was 0.3 parts, the surface drying time and deep curing effect were relatively excellent, but the mixing of the two catalysts can increase the elongation at break of the colloid and improve the toughness. The ratio needs to be adjusted according to actual use and customer needs.
[0049] Embodiment 3
[0050] 1. Mix hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide and magnesium hydroxide for 30 minutes, add silicone oil, mix evenly, heat the planetary mixer to 135°C and mix again in vacuum for 2 hours, the vacuum degree is -0.098MPa, and cool naturally to about 35°C to obtain colloid A;
[0051] Among them, hydroxyl-terminated dimethylsiloxane uses 18000Pa·s, the addition ratio is 100 parts, heavy calcium carbonate is added in a ratio of 20 parts, light calcium carbonate is added in a ratio of 80 parts, titanium dioxide is added in a ratio of 10 parts, magnesium hydroxide is 0.2 parts, and silicone oil is selected to be 100Pa·s, and the addition ratio is 5 parts.
[0052] 2. In a dual planetary power mixer, add white carbon black and a crosslinking agent to colloid A in two batches at intervals of 30 minutes, and stir in vacuum for 1 hour to obtain colloid B; wherein the white carbon black is fumed white carbon black, hydrophobic type, with an amount of 3 parts, and the crosslinking agent is 2 parts of methyl tributylidene oxime silane.
[0053] 3. After mixing the coupling agent, catalyst and acetylacetone, add them to colloid B, and stir for 1 hour to obtain colloid C, which is the finished one-component photovoltaic structural sealant; wherein the coupling agent is vinyltrimethoxysilane, the addition amount is 3 parts, the catalyst is dibutyltin diacetate, the amount is 0.3 parts, and acetylacetone is a dissolving aid, the amount is 0.3 parts.
[0054] The test results of the above photovoltaic adhesive are as follows:
[0055]
[0056] Comparative Example Performance of commercially available photovoltaic structural adhesives that are considered to have good performance:
[0057]
[0058]
[0059] Comparison conclusion: By comparing the experimental data with a certain brand of photovoltaic structural adhesive on the market, the main differences are reflected in the tensile strength, elongation at break and compatibility with the substrate. The adhesiveness and adhesion test of the sealant of the present invention are significantly higher than those of the existing structural adhesive. The main core of the photovoltaic structural adhesive of the present invention is high strength, high elongation at break, and excellent adhesion to the substrate. The curing speed of the present invention is 3.4mm, while the curing speed of the existing similar photovoltaic adhesive is 2.4mm. The present invention increases the curing depth by about 30%. Generally, the construction thickness of photovoltaic adhesive structural adhesive does not exceed 3mm, that is, the present invention can be completely cured within 1 day, and can basically complete the curing within one day and enter the next stage of the process. Similarly, the curing speed slows down as the depth increases. The curing time of the existing photovoltaic adhesive takes 2-3 days.
[0060] The present invention cooperates with components of different proportions and different types, and the finished products obtained after the test are tested. It is found that in the application environment of photovoltaic glue, the surface drying time and deep curing effect of the product of the present invention are relatively excellent, and the elongation at break of the colloid can be increased, and the toughness can be improved. Further, the product of the present invention improves the efficiency required for industrial production, and the curing depth of the photovoltaic glue product is good at different temperatures and humidities. It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not used to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range and any other stated value or each smaller range between the intermediate values within the range are also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the range. Without departing from the scope or spirit of the present invention, various improvements and changes can be made to the specific embodiments of the present invention specification, which is obvious to those skilled in the art. Other embodiments obtained from the description of the present invention are obvious to technicians. The present invention description and examples are only exemplary.
Claims
1. A one-component photovoltaic structural sealant, comprising hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, a cross-linking agent, a coupling agent, a catalyst, and a dissolving aid.
2. The one-component photovoltaic structural sealant according to claim 1, characterized in that: The viscosity of hydroxy-terminated dimethylsiloxane is 15000 Pa·s to 18000 Pa·s; the viscosity of silicone oil is 100 Pa·s to 200 Pa·s.
3. The one-component photovoltaic structural sealant according to claim 1, characterized in that: The white carbon black is a hydrophobic white carbon black; the crosslinking agent is selected from one or more of methyl tributylacetoximate silane, vinyl tributylacetoximate silane and methyl triethoxy silane.
4. The one-component photovoltaic structural sealant according to claim 1, characterized in that: The coupling agent is one or more of vinyl trimethoxysilane, γ-(2,3-epoxypropoxy)propyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-n-butyl-3-aminopropyl trimethoxysilane, and aminosilane polymer; and the catalyst is an organic tin compound.
5. The one-component photovoltaic structural sealant according to claim 1, characterized in that: The weight ratio of hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide, silicone oil, white carbon black, crosslinking agent, coupling agent, catalyst and dissolution aid is 100: (10-30): (70-90): (10-15): (0.1-0.3): (10-15): (1-3): (1-5): (1-5): (0.1-0.5): (0.1-0.5).
6. The method for preparing the one-component photovoltaic structure sealant according to claim 1 comprises the following steps: mixing hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, silicone oil, white carbon black, a cross-linking agent, a coupling agent, a catalyst, and a dissolving aid to obtain the one-component photovoltaic structure sealant.
7. The method for preparing the one-component photovoltaic structure sealant according to claim 6, characterized in that: The method comprises the following steps: hydroxyl-terminated dimethylsiloxane, heavy calcium carbonate, light calcium carbonate, titanium dioxide, magnesium hydroxide and silicone oil are mixed in vacuum to obtain colloid A; then white carbon black and a cross-linking agent are added to colloid A, and the mixture is stirred in vacuum to obtain colloid B; then a coupling agent, a catalyst and a dissolving aid are added to colloid B to obtain colloid C, and colloid C is continuously vacuumed to obtain a single-component photovoltaic structure sealant.
8. A solar panel, using the single-component photovoltaic structural sealant according to claim 1 as an adhesive.
9. Application of the one-component photovoltaic structural sealant according to claim 1 in photovoltaic bonding.
10. Use of the one-component photovoltaic structural sealant according to claim 1 in the preparation of solar energy adhesive materials.